2019
DOI: 10.1001/jamanetworkopen.2019.8090
|View full text |Cite
|
Sign up to set email alerts
|

National Trends in Colorectal Cancer Incidence Among Older and Younger Adults in Canada

Abstract: Key Points Question Is the incidence of colorectal cancer among younger adults still increasing in Canada? Findings This cohort study used data from comprehensive Canadian national cancer registries and included all 688 515 incident colorectal cancers diagnosed from 1969 to 2015. The incidence of colorectal cancer among younger adults increased from 2006 to 2015 among men with an annual percentage change of 3.47% and from 2010 to 2015 among women with an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
80
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 15 publications
(32 reference statements)
3
80
0
1
Order By: Relevance
“…Cancer is generally considered a disease of aging, with only approximately 10% of all new cases in Canada being diagnosed before the age of 50 years 1 . However, recent reports have shown that colorectal cancer is increasing disproportionately in young adults, with successively younger generations at higher risk 2,3 . Other cancers, including multiple myeloma and cancers of the uterine corpus, gallbladder, kidney, and pancreas, have exhibited similar increases among young adults 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is generally considered a disease of aging, with only approximately 10% of all new cases in Canada being diagnosed before the age of 50 years 1 . However, recent reports have shown that colorectal cancer is increasing disproportionately in young adults, with successively younger generations at higher risk 2,3 . Other cancers, including multiple myeloma and cancers of the uterine corpus, gallbladder, kidney, and pancreas, have exhibited similar increases among young adults 2 .…”
Section: Introductionmentioning
confidence: 99%
“…(21) Simultaneously, an increase in CRC rates among younger adults <50 years of age is reported. (1,2,4) Regular screening for CRC is recommended by the U.S. Preventive Services Task Force (USPSTF) beginning at age 50. (22) Due to the large‐scale screening programs in these patients >50 years of age with removal of precancerous polyps during colonoscopy and earlier detection of CRC, the incidence and mortality of CRC has declined.…”
Section: Systemic Metabolic Dysfunction and Its Link To Colorectal Camentioning
confidence: 99%
“…Colorectal cancer (CRC) is one of the most common causes of cancer‐related death in the USA and its incidence among young adults has increased over the last several decades. (1‐4) Simultaneously, the proportion of overweight and obese children and adolescents is rising, suggesting an association between metabolic dysfunction and carcinogenic mechanisms. (4‐7) A direct association between obesity and early‐onset CRC was found among young women as part of the The Nurses' Health Study II.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Also a recent trend is the increased risk of CRC among individuals less than 50 years, with an APCi of 4.45% for women less than 50 years since 2010 and APCi of 3.74% for men less than 50 years from 2006 through 2015. [2] The physical (e.g. pain, disability) [3,4] and psycho-social (e.g.…”
Section: Introductionmentioning
confidence: 99%